2011
DOI: 10.1590/s0100-69162011000500003
|View full text |Cite
|
Sign up to set email alerts
|

Climate variations in greenhouse cultivated with gerbera and relationship with external conditions

Abstract: Black meshes used in greenhouses provide shade to plants, affecting photosynthesis and presenting certain properties that change the microclimatic conditions in these environments. The objective of this study was to evaluate the variation in climate elements in greenhouse cultivated with gerbera (Gerbera jamesonii, Vr. Rambo) in relation to external conditions and the reference evapotranspiration (ETo) at Teresina, State of Piauí, Brazil. The measurements were obtained from July to October 2007 by an automatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
1
0
1
3
Order By: Relevance
“…Similar results for temperatures between the non-acclimatized protected environments (greenhouse and screened buildings) were observed by COSTA et al (2010b) in papaya seedlings and COSTA et al (2011b) in the formation of yellow passion fruit seedlings. Values of external temperatures and indoor relative humidity in the environment showed no discrepancy, different from that observed by ANDRADE JÚNIOR et al (2011) for the relative humidity of internal air of an environment with 50% shading and the external temperature.…”
Section: Resultscontrasting
confidence: 91%
“…Similar results for temperatures between the non-acclimatized protected environments (greenhouse and screened buildings) were observed by COSTA et al (2010b) in papaya seedlings and COSTA et al (2011b) in the formation of yellow passion fruit seedlings. Values of external temperatures and indoor relative humidity in the environment showed no discrepancy, different from that observed by ANDRADE JÚNIOR et al (2011) for the relative humidity of internal air of an environment with 50% shading and the external temperature.…”
Section: Resultscontrasting
confidence: 91%
“…Several authors conducted experiments similar to those in this study and did not observe major differences in RH between covered environments and outside conditions (Cardoso et al 2008;Chavarria et al 2009;Pedro Júnior et al 2011). Some authors observed opposite results in vineyards, which means lower RH under plastic covers than in the external condition, especially during daytime periods (Andrade Júnior et al 2011) or higher RH in covered environments than in the open field (Novello et al 2000). Thereby, RH was lower under BSS than in BPF, especially for RHmin and RHmax.…”
Section: Discussionsupporting
confidence: 73%
“…Ou seja, em termos percentuais, a ETo sob a cobertura correspondeu a 77,8; 75,0 e 82,4% da ETo obtida pelos métodos de PM, TCA e J&H, respectivamente; e 105 e 131,3% da ETo obtida pelos métodos de H&S e Mak, respectivamente. Percebe-se que, com exceção dos métodos de Hargreaves e Samani e Makkink, a evapotranspiração no ambiente protegido foi menor do que aquela que ocorreu no exterior; isso, devido à atenuação da radiação solar sob a cobertura e alterações nas condições de temperatura, umidade relativa do ar e da redução da ação dos ventos, principais fatores da demanda evaporativa da atmosfera (DALMAGO et al, 2006;REIS;SOUZA;AZEVEDO, 2009;PIVETTA et al, 2010;ANDRADE JÚNIOR et al, 2011). Embora, geralmente, a evapotranspiração no interior dos ambientes protegidos seja menor do que a campo aberto (ANDRADE JÚNIOR et al, 2011), os resultados encontrados no presente estudo para a ETo obtida pelo método de H&S podem ser justificados, considerando que a temperatura, única variável de entrada do método, foi maior sob a cobertura do que no exterior ( Figura 3A), condição esta que, associada ao efeito de outros parâmetros, contribuíram para ETo mais elevada sob a cobertura.…”
Section: Figuraunclassified